2019
DOI: 10.18203/2349-2902.isj20191880
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia: predictive factors, clinical presentation and management

Abstract: Background: Incisional hernia is an iatrogenic complication of abdominal surgery and an important cause of morbidity. It occurs in 11-20% of the patients after abdominal surgery. The present study aimed to evaluate predictive factors associated with causation of incisional hernia, clinical presentation, modalities of management and their post-operative complications.Methods: In a hospital based observational study, the subjects were diagnosed cases of incisional hernias with or without comorbidities undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This prospective study was conducted at department of general surgery in tertiary care institute over period of one year. In present study, most of the patients with incisional hernia had reported in fifth decade with mean age of the patient was 44.98 years which is comparable with the other studies [7,8] . Increased incidence above the age of 40 years may be attributed to gradual decrease in abdominal muscle tone with the increasing age.…”
Section: Discussionsupporting
confidence: 90%
“…This prospective study was conducted at department of general surgery in tertiary care institute over period of one year. In present study, most of the patients with incisional hernia had reported in fifth decade with mean age of the patient was 44.98 years which is comparable with the other studies [7,8] . Increased incidence above the age of 40 years may be attributed to gradual decrease in abdominal muscle tone with the increasing age.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported most commonly in large incisional hernias or recurrent groin hernias where a thinned-out skin vitiates the mechanism for the evisceration [ 3 ]. It is usually precipitated by a thin hernia sac and atrophic avascular skin, which causes friction and desquamating dermatitis, leading to ulceration and gaping [ 4 ]. The phenomena are propagated by multiple risk factors like bouts of coughing, straining during defecation, heavy weight-lifting, older age, obesity, malignancy and history of wound infection, and repeated wound debridement following initial surgery, which adds on to the causality in the form of a sequential increase in the centrifugal intra-abdominal pressures [ 5 ].…”
Section: Discussionmentioning
confidence: 99%